Indonesia’s National Resilience through Adaptive Defense Governance in the Era of Hybrid Warfare - Delfiazi Puji Lestari; Tsulis Amiruddin Zahri (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2026)
The evolution of hybrid warfare has fundamentally reshaped national security threats from conventional military confrontation into multidimensional challenges involving cyberattacks, disinformation, economic coercion, and ideological influence. While previous studies have primarily examined defense modernization, military strategy, or cybersecurity separately, limited attention has been paid to how defense institutional transformation can strengthen national resilience through a public administration and governance perspective. This study aims to analyze the transformation of Indonesia’s defense institutions in responding to hybrid warfare and to develop an adaptive defense governance model that integrates defense, governance, and national resilience. Employing a qualitative descriptive-analytical design, the study analyzes government regulations, strategic policy documents, institutional reports, and peer-reviewed literature using thematic analysis to identify patterns of institutional adaptation and governance transformation. The findings reveal four strategic dimensions of adaptive defense governance: (1) institutional adaptation through the establishment of the National Defense Council, (2) strengthened inter-agency coordination based on a whole-of-government approach, (3) integration of cyber defense and digital resilience into the national defense system, and (4) collaborative civil–military governance to enhance multidomain resilience. Nevertheless, institutional fragmentation, overlapping authority, limited policy interoperability, and weak strategic coordination remain significant barriers to effective implementation. This study contributes by proposing an adaptive defense governance framework that extends existing defense governance literature through the integration of national resilience, collaborative governance, and hybrid warfare perspectives. Practically, the proposed framework provides policy guidance for strengthening institutional coordination and developing a more integrated, adaptive, and resilient national defense system in addressing future hybrid threats.